Branding consciente: o desafio da gestão de marcas para o século XXI (ModaPalavra e-periódico, 2010)
This paper deals with a relevant theme in the present business society: the trademark management. Due to the market language which focused on simbols and signals appropriated to the products available to the consumers, it is necessary that the companies invest in this sector. Concerning this issue, this study seeks to deepen in the aspect of biodiversity as a conscious branding, because it refers to the trademark management with social responsibility and sustainable development. In this view, the trademark management serves as a counterpoint to the discussion that needs to be done regarding the development of trademarks in relation to universal precepts of conservation and life maintenance by means of a new management alternative: the conscious branding that is seen as an environment supporter.
Keywords: Branding; Fashion; Sustainability